CONTINUING EDUCATION – WHAT IS ALL THE FUSS ABOUT? - Farley, Margaret (Operating Room Nurses Association of Canada Journal, 2004)
Advances in medicine and technology are demanding increased, and more diverse, education and learning. To provide quality patient care perioperative nurses need to be up to date. Is it possible to accomplish this task in our era of healthcare staff shortages and budget cuts? Step outside the traditional classroom and see where it leads. Continuing education, or mandatory education hours are also requirements for a growing number of professional bodies. Can we continue to meet this demand?